A retrospective study on endoscopic missing diagnosis of colorectal polyp and its related factors - Lou, Guo-Chun; Yang, Jian-Min; Xu, Qi-Shun; Huang, Wei; Shi, Shu-Ging (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: To investigate missing diagnosis of the polyp by colonoscopy, and to reveal the endoscopic, pathological features of missed polyps and related factors inducing missing diagnosis. Materials and Methods: We reviewed the data of the patients who received colonoscopy twice within 180 days. The missing rate of the colorectal polyps ware calculated and the endoscopic and pathological features of the missed polyps were summarized. Possible related factors inducing the missing diagnosis were analyzed. Results: The missing rate of colorectal polyps in this study was 27.7%, with as high as 11.5% missing rate of advanced polyps. Most missed polyps were those of <5 mm in diameter (55.2%) or flat ones (75.9%). Most of missed polyps are located in the rectum (21.8%), sigmoid (41.4%) and transverse colon (17.2%). No significant correlation was observed between the missing rate and colonoscopic manners (p>0.05), neither between the missing rate and operators (p>0.05). But number of basal polyps was proved to be significantly correlative with number of missed polyps (r=0.694, p<0.001). Conclusion: Polyps of <5 mm in diameter or flat polyps are more likely to be missed in the endoscopy. Most of missed polyps are located in rectum, sigmoid and transverse colon. More basal polyps usually accompany with more polyps missed.